(untitled) (Applied Biological Research, 2024)
Annona glabra L. (family: Annonaceae) is used as a traditional medicine against several human infirmities, including cancer. Most of the members of family annonaceae possess a unique class of natural product called acetogenins. The present study was aimed to extract and fractionate the acetogenins from the leaves of Annona glabra using the solvents of increasing polarity, such as hexane, chloroform, ethyl acetate ethanol, and water. Solvents with higher polarity such as ethyl acetate were found more effective in extracting lactone-containing compounds as compared to the less polar solvents. The quantity of acetogenins isolated from the A. glabra leaves was estimated by lactone concentration test. LC-MS/MS screening showed the presence of acetogenins in the samples with m/z values 596.9, 606.9, 679.8, 566.8, 550.85, 672.15, 672.15, 624.9 and 565.35. These findings open up effective methods for separation and quantification of bioactive compounds. Further studies are to be focused on evaluating the efficacy of these compounds in pre-clinical and clinical trials, which may potentially contribute in developing the novel therapeutic formulations.